Medical Waste Management in Primary HealthCare Centers and Private Clinics: Jenin District as a Case Study - Majdi Qasem Jameel Abu-Awwad (My University, 2008)
This study was carried out during the period from March to October 2007 in Jenin district, aimed to review the current situation of the management of the medical wastes (M.W.) that is generated in the primary health care centers (PHCs) and private clinics (Pr.C.). The study showed in Jenin district lack of administration of medical waste capabilities, technical and financial ability for a good and strong management of medical wastes, and lack of joint cooperation between the governmental organizations responsible for the health sector in Jenin district as Ministry of Heath, Ministry of Local Governance, Palestinian Environmental Quality Authority and other organizations. The study showed also that most workers in the public services sector do not follow the proper methods of transferring of medical waste, indicating urgent need for the education and training on a right basis and safe methods for the dealing process with medical wastes. The second part of this study shows that PHCs generate an average 0.830 kg. Of medical waste per primary health care center per day, where was the average of generated medical waste of private clinic about 0.350 kg. per private clinics per day. Therefore, the annual generation rate of MW in Jenin district from primary health care centers and private clinics could reach more than 61 tons / year of hazardous materials generated in the district. These results indicate a clear evidence for the need for a good management of medical wastes in Jenin district that can preserve the human health and the clean environment.

أنجزت هذه الدراسة خلال الفترة الواقعة بين شهري آذار و تشرين أول 2007 في محافظة جنين، من أجل تقيم واقع إدارة المخلفات الطبية في مراكز الرعاية الصحية الأولية والعيادات الخاصة، وتحديد حجم النفايات الطبية المنتجة في محافظة جنين. أظهرت الدراسة عدد من النتائج أهمها: ضعف حضور إدارة النفايات الطبية في المحافظة، شح الإمكانيات والمقومات المادية والفنية اللازمة لإدارة صحيحة للنفايات الطبية، ضعف التعاون المشترك بين المؤسسات ذات العلاقة الحكومية وغير الحكومية المسئولة عن القطاع الصحي في المحافظة مثل ( وزارة الصحة الفلسطينية، والحكم المحلي، وسلطة جودة البيئة الفلسطينية). كذلك أظهرت الدراسة أن أكثر العاملين في قطاع الخدمات العامة( المراسلين وعمال النظافة ) ليس لديهم فكرة عن أسس التعامل السليم والنقل المناسب للنفايات الطبية، مع حاجتهم الماسة للتوعية والتدريب على الأسس السليمة والآمنة للتعامل مع النفايات الطبية. كما اشتملت الدراسة على معرفة حجم النفايات الطبية المنتجة من مراكز الرعاية الصحية الأولية والعيادات الخاصة في محافظة جنين ونوعها ووزنها، ووجد أن إنتاج المراكز الصحية من المخلفات الطبية يبلغ (0.831)كيلو غرام / مركز رعاية صحي أولي/ يوم ، في حين أن إنتاج العيادات الصحية الخاصة من النفايات الطبية بلغ (0.350) كيلوغرام /عيادة خاصة /يوم. بلغ معدل إنتاج مراكز الرعاية الصحية الأولية والعيادات الخاصة للنفايات الطبية في محافظة جنين 62 طن تقريبا سنويا من النفايات الطبية. تقدم هذه النتائج الدليل الواضح على أهمية وجود إدارة مناسبة للنفايات الطبية في محافظة جنين؛ لتحافظ على صحة الإنسان والبيئة.
إدارة النفايات الطبية في مراكز الرعاية الصحية الأولية والعيادات الخاصة في محافظة جنين